Character, Writing, and Reputation in Victorian Law and Literature - Frank, Cathrine O. (Edinburgh Critical Studies in Law, Literature and the Humanities Ser., 2022)
Drawing on primary sources including novels, Victorian periodical literature, legislative debate, case law and legal treatise, Cathrine O. Frank traces the ways conventions of literary characterisation mingled with character-centred legal developments to produce a jurisprudential theory of character that extends beyond the legal profession.